Primary congenital glucoma - Chafloque-Cervantes, Augusto B. (2023)
Primary congenital glaucoma (PCG) or primary infantile glaucoma (PIG) is a rare disease that presents a characteristic clinical picture with a clear identity. Because it is primary, it has no association with other syndromes and ocular anomalies, with increased intraocular pressure (IOP) due to poor development of the excretory part of the aqueous humor drainage, in the structures of the trabecular meshwork, ergo PCG is a product of poor development from the tissues of the angle of the anterior chamber that are embryologically derived from neural crest cells. Its rare presentation, with recessive inheritance of variable penetrance and very likely multifactorial inheritance makes it difficult for its study, follow-up and treatment that is focused on lowering IOP as soon as possible, preparing the child for surgery. Classically the initial surgery can be goniotomy or trabeculotomy. The failure of these procedures inserts the case as refractory with little studied protocol and is the heritage of combined surgeries such as trabeculectomy coupled with trabeculotomy, trabeculectomy with application of antimetabolites, trabeculectomy with amniotic membrane, placement of implants or valved devices and last and more invasive, procedures that destroy the ciliary body. Ethics obliges us to follow these cases to the end. When surgery is not efficient, visual rehabilitation, correcting the resulting refractive errors and addressing the opacities of the eye's transparent media, and finally we must combat visual loss due to amblyopia in all its forms.